Computer-aided colour harmony design based on artificial physics optimisation. (2015) - Yang, Gangjun; Zhang, Xueliang
The colour harmony design can be regarded as a combinatorial optimisation problem. As a novel population-based stochastic algorithm inspired by artificial physics, APO is applied to colour harmony design. Firstly, the paper constructs the mathematical model of colour harmony theory according to Munsell's theories of colour harmony. Then, the colour harmony aesthetics measure is regarded as the object function to be optimised, and the colours do not fall into the Moon and Spencer ambiguity region and are satisfied with the balance of colour patch, which are the constrained conditions. When APO is used to solve the problem, each feasible colour is regarded as an individual. The higher the aesthetics measure, the bigger the mass of the individual, which has a bigger force to other individuals with lower aesthetics measure. Driven by the attractive-repulsive rule, the population can search the better region of the higher aesthetics measure value. Finally, the APO algorithm used in the colour harmony design of machine tool shows the effectiveness of the proposed method.